THE CORRELATION BETWEEN VOCABULARY MASTERY AND STUDENT’S SPEAKING ABILITY - Hafid Sabila; Luh Ketut Sri Widhiasih; IGA Putri Wirastuti (Academic Journal on English Studies (AJOES), 2022)
This research aimed at finding out the correlation between vocabulary mastery and student speaking ability of SMK Saraswati 1 Denpasar in academic year 2020/2021. The present study used an ex post facto research with correlational design. The samples of the research were 31 students of tenth grade selected by using random sampling with lottery system. There were two research instruments which were used to collect the data. It was close task as vocabulary instrument and a short describing monologue as the speaking test. Based on the results of Pearson Product Moment Correlation and T-test, the researcher confirmed that the directional hypothesis was accepted. In conclusion, there is a significant correlation between vocabulary mastery and speaking ability of the tenth grade student of SMK Saraswati 1 Denpasar in academic year 2020/2021.